How an evidence synthesis program's growth has supported research use and learning community partnership networks within a learning health system: A descriptive analysis and case series - Isomi Miake‐Lye; Selene Mak; Tom Valente; Nicole Floyd; Paul Shekelle (Learning Health Systems, 2025)
Abstract Introduction The Veterans Administration Evidence Synthesis Program (VA ESP) was established in 2007 to support evidence‐based decisions about policies and programs in the VA healthcare system and has served as a critical component in the VA learning health system. Our objective was to document the growth of the ESP partner network and key policy and practice impacts of the program through a descriptive social network analysis and case series. We also aimed to provide insights into key features of some successful partnerships and the role evidence synthesis can play in supporting the improvement of the health system. Methods Using social network analysis and national ESP program data, we depicted the network at its initial, fully operational, and established phases of development to describe over a decade of ESP partnerships. We also queried program leadership and ESP partners about their collaboration experiences to generate a case series that demonstrates key examples of successful partnerships. Results Of the 82 partner offices for whom the ESP has generated a report, over half (66%, n = 54) collaborated with the ESP on multiple projects, having received two or more synthesis products over time. Case studies revealed the impacts of ESP evidence synthesis on policy and practice, how our partners used the evidence generated from these processes, and the future work spawned from these efforts. While infrastructure and formal mechanisms can support these connections, relationships and partnering are instrumental facets as well. Conclusion Partnerships between the ESP and decision‐makers can facilitate access to evidence and leadership's ongoing use of this evidence. The ESP has led to meaningful, evidence‐driven communication between research and operational partners and has supported stakeholders in informing policy and system change.